Mo-Ni and organic carbon isotope signatures of the mid-late Mesoproterozoic oxygenation. (15th April 2020) - Ansari, Arif H.; Ahmad, Shamim; Govil, Pawan; Agrawal, Shailesh; Mathews, Runcie P.
Graphical abstract: Highlights: Surface layer of the mid-late Mesoproterozoic hydrosphere was oxic. Primary productivity was dominant in the terrestrial hydrosphere. The terrestrial hydrosphere offered best condition for complex eukaryotic evolution. Abstract: This study performed a redox sensitive trace element (RSTE) and organic carbon isotope investigation on the shallow section of ~1.2 Ga Bijaigarh Shale, Kaimur Group, Vindhyan Supergroup. The results demonstrate that unlike the coeval deeper section, in which Mo and Ni concentrations are several-folds higher compared to the upper continental crust (UCC), the shallow section contains Mo and Ni equivalent to the upper continental crust (UCC). This spatially heterogeneous burial of Mo and Ni is very similar to the modern stratified basins i.e., Black Sea and Cariaco Basin, where Ni and Mo composition of the sediments underlying a shallow oxic water column is comparable to the UCC however, the deeper sediments underlying the anoxic/euxinic contains several folds-higher Mo and Ni compared to the UCC. Bulk precipitation of Mo in a hydrosphere is mainly controlled by sulphide present in the anoxic/euxinic layers of the water column, on the other hand, Ni precipitation is generally controlled by oxygenic primary productivity. Though the shallow section of the Bijaigarh Shale is depleted in Ni, a significant correlation between Ni and TOC is still relevant and indicates an oxygen-rich surface water layer for the respective palaeohydrosphere. Furthermore, δ 13 C-org values (between −32.0 and −30.4‰) from the shallow section suggests that the organic carbon exported into the sediments during the Bijaigarh Shale deposition was primarily derived from oxygenic photosynthesis in the concurrent surface water layers.